Application of the Fair Use Principle to Songs Modified on Digital Platforms Based on Positive Law in Indonesia - Elsha Yoleda; Rika Ratna Permata; Tasya Safiranita Ramli (Universitas Widya Gama Malang, 2023)
The song entitled